Investigation of Al back contacts and BSF formation by in situ TEM for silicon solar cells. (26th December 2012) - Park, Sungeun; Song, Jooyoung; Tark, Sung Ju; Kim, Young Do; Choi, Chel‐jong; Kwon, Soonwoo; Yoon, Sewang; Son, Chang‐Sik; Kim, Donghwan
ABSTRACT Back contacts for Si solar cells made by Al evaporation and screen printing Al paste were studied by transmission electron microscopy. Si was found to diffuse into the Al during heating. Si diffusion formed vacancies in the Si wafer and Al could then penetrate the Si wafer in spiked formations. The Al spikes retracted during cooling, leaving a doped back surface field region. Copyright © 2012 John Wiley & Sons, Ltd.